Risk of Viral Hepatitis B and C Among Young Adolescents Who Inject Drugs: A Future Public Health Challenge - Varada Jayant Madge; E. K. Vinayakan; Rishi Garg; Sunil Mehra (Social Medicine Publication Group, 2018)
Background: Adolescents are vulnerable populations and due to lack of health information on injecting drugs and viral hepatitis, it is likely that they could engage into unsafe injection and sexual practices that could be risky for their health. Aim: The present paper is an attempt to explore the risky patterns that make adolescents vulnerable to Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV). The adolescents were part of the intervention, "Prevention and Early Management of Hepatitis B and C among high risk group in Amritsar and Imphal, India", that was conducted from October 2014 till January 2018 Material and methods: In this intervention, 29 [out of 1700 People Who Inject Drugs (PWID] were adolescents. Risk assessment tool was used to monitor their health condition and adherence to harm reduction practices. Since the number was small, simple frequency distribution (number and per cent) was used to analyse the data and numbers are used to elucidate the overall results. Results: Overall the findings showed that out of 29 adolescents, 25 of them were actively engaged in sexual practices and most of them did not use protective mechanisms like condoms. Seven were injecting more than 30 shots per day and eight adolescents mentioned that they shared needles. Three adolescents in this intervention, were diagnosed with HCV positive and were linked to treatment during the project period. Four adolescents showed symptoms of STI and were treated for the same in the past one year. Conclusion: The findings suggests targeting the young population for intervention by providing continuous education sessions on harm reduction practices and follow up to reduce the risk of transmission of HBV and HCV.